2021
DOI: 10.3390/ijms22073752
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of ZNF71 KRAB in Non-Small-Cell Lung Cancer

Abstract: Our previous study found that zinc finger protein 71 (ZNF71) mRNA expression was associated with chemosensitivity and its protein expression was prognostic of non-small-cell lung cancer (NSCLC). The Krüppel associated box (KRAB) transcriptional repression domain is commonly present in human zinc finger proteins, which are linked to imprinting, silencing of repetitive elements, proliferation, apoptosis, and cancer. This study revealed that ZNF71 KRAB had a significantly higher expression than the ZNF71 KRAB-les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 70 publications
2
26
0
Order By: Relevance
“…A recent meta-analysis showed that gefitinib and erlotinib have comparable effects on patient survival, overall response rate, and disease control rate, with no considerable variation with regard to EGFR mutation status, ethnicity, line of treatment, and baseline brain metastasis status [ 33 ]. EGFR mutation in the studied NSCLC cell lines was provided in our previous study [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis showed that gefitinib and erlotinib have comparable effects on patient survival, overall response rate, and disease control rate, with no considerable variation with regard to EGFR mutation status, ethnicity, line of treatment, and baseline brain metastasis status [ 33 ]. EGFR mutation in the studied NSCLC cell lines was provided in our previous study [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Emerging evidence links epithelial to mesenchymal transition (EMT) to tumor progression, metastasis, and resistance to cancer therapy [ 15 , 16 , 17 , 18 ]. We reported that ZNF71 KRAB isoform was associated with EMT in NSCLC tumors and cell lines [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…TRIM28 contributes to EMT and might be involved in lung cancer metastasis [ 25 ]. We previously reported that ZNF71 KRAB was associated with EMT and patient outcomes [ 19 ]. Nevertheless, the function of ZNF71 KRAB in EMT is not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Included in this 7-gene assay, CD27 and ZNF71 had concordant mRNA and protein expression in NSCLC tumors [12]. Our recent study showed that ZNF71-KRAB, the KRAB isoform that is transcriptional repression, was associated with EMT in NSCLC tumors and cell lines [119]. CD27, an emerging ICI [13], is being tested as adjuvant therapy in phase I/II clinical trials for multiple tumor types with promising results [14,15].…”
Section: Discussionmentioning
confidence: 95%